Natural conditions and environmental impacts in a coastal hydrographic basin in the Brazilian Amazon - Gorayeb, A.; Lombardo, M. A.; Pereira, L. C.C. (My University, 2011)
The main focus of this paper was an integrated analysis of the Caeté hydrographic basin, in eastern Amazonia, and the evaluation of the levels of environmental degradation. The study was based on a landscape approach, with four main technical stages: literature and cartographic research; questionnaire-based interviews in the field; laboratory analyses of water quality; data analysis. The main problems in the region include the lack of public sanitation, unregulated land ownership, inadequate management of forestry resources, conflicts over access to water resources, and the indiscriminate exploitation of subterranean water sources. The environmental problems observed within the study area contribute to negative social processes, such as the loss of traditional cultural values and a decline in environmental sensitivity. Reversing such problems will require fundamental changes in national and international policies, and the socio-economic structure of Amazonian populations. It is hoped that the present study will contribute to the demystification of the popular image of the region, reinforced by the international media, as a vast area of exuberant and homogeneous vegetation, exotic animals, and low population densities, in which the major problem is the ongoing increase in deforestation levels. The Amazon region is, in fact, far more complex than this common stereotype suggests. In this sense, the Amazon basin, and especially its coastal zone, must be understood as a complex and diverse region, with a differentiated array of problems and capabilities, which requires an integrated approach to the solution of social and environmental questions.
Keywords: Brazilian Amazon coast; Management; Water quality